Avaliação do comportamento de lisímetros preenchidos com resíduos sólidos com diferentes características - Moreira Júnior, Francisco Amílcar (2015)
This research aimed to evaluate the behavior of the mass of solid waste in terms of leachate production, gas generation, evaluation of the physicochemical properties of the effluent, waste characterization and discharge for three lysimeters in an area belonging to the Landfill Metropolitan West Caucaia - CE. The survey was conducted during the months from January to June 2014, continuing the monitoring and characterization of the properties occurring internally to lysimeters since its inception in May 2012. It was used to evaluate three lysimeters: L01 - filled with 100% of waste in the way reach the landfill; L02 - filled with 50% of organic waste and 50% as they arrive to the landfill; L03- 100% filled with organic waste. During the research period was a survey of rain in the city belonging to the landfill in order to verify the possible interference in the generation of gases and waste production. As a result was observed consistency in the production of biogas, especially in the observed values of methane at the base of the lysimeters, more intensely, the L03, as well as the great generation of leachate, with the drawback of odor produced by hydrogen sulfide gas. As they were already there about two years in operation were high discharge values of waste, and achieved an average of 92 cm for the L01, 130.5 cm to L02 and 123.75 cm for the L03. In terms of methane production, the values obtained were 0.726% and 0.667% for the base and the middle of L01, 2.81% and 0.69% at the base and in the middle of L02, and 4.8 % and 1,966% in the vicinity of the base and the middle of the L03. For carbon dioxide the values obtained, on average, to the base of the lysimeters and the middle was 2.041% and 0.132% in the L01, and 3.28% to 0.4% and 7.8% and L02 2,778 % in the L03. As for the hydrogen sulfide was obtained values of 0.866 ppm and 0.917 ppm for L01, 5.14 ppm and 0.87 ppm for L02, and 164.2 ppm to 4,377 ppm at the bottom and in the middle of L03 respectively. In terms of physical and chemical characteristics of the leachate, variations were found for certain parameters, especially during the months of highest rates of rainfall, affecting in this way, the waste mass characteristics, the activity of microorganisms and the effluent generation, which performed with values well above the permitted in specific legislation for the release in water bodies. Even with the presence of adversity, such as excessive repression, strong production of liquid two years to decompose, and cracks in the cover layer, was found also a good gas production, indicating the viability and importance of investing in biogas production technologies in landfills.